1995
DOI: 10.1182/blood.v86.7.2724.bloodjournal8672724
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the CDKN2 (MTS1/p16ink4A) gene in primary B-cell lymphomas

Abstract: The CDKN2 gene located on chromosome 9p21 encodes the cyclin-dependent kinase-4 inhibitor p16. This gene is a putative tumor-suppressor gene because of its frequent alterations in many kinds of tumor cell lines. We analyzed the CDKN2 gene to evaluate its alterations in 52 primary specimens of non-Hodgkin's lymphoma (NHL) or chronic lymphocytic leukemia (CLL) of B-cell origin by Southern blot analysis, polymerase chain reaction-mediated single-strand conformation polymorphism (PCR-SSCP) analysis, and direct seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…Alterations in the CDKN2 gene have frequently been found in acute lymphocytic leukaemia (ALL) (Cayuela et al, 1996;Ogawa et al, 1995;Ohnishi et al, 1995;Quesnel et al, 1995), especially the T-cell phenotype (Schröder et al, 1995;Siebert et al, 1995), but rarely in acute myelogenous leukaemia Nakamaki et al, 1995). Furthermore, we found, as did other investigators, that changes in the CDKN2 gene may contribute to tumourigenesis in some patients with non-Hodgkin's lymphoma (NHL) (Koduru et al, 1995;Uchida et al, 1995).…”
supporting
confidence: 73%
See 4 more Smart Citations
“…Alterations in the CDKN2 gene have frequently been found in acute lymphocytic leukaemia (ALL) (Cayuela et al, 1996;Ogawa et al, 1995;Ohnishi et al, 1995;Quesnel et al, 1995), especially the T-cell phenotype (Schröder et al, 1995;Siebert et al, 1995), but rarely in acute myelogenous leukaemia Nakamaki et al, 1995). Furthermore, we found, as did other investigators, that changes in the CDKN2 gene may contribute to tumourigenesis in some patients with non-Hodgkin's lymphoma (NHL) (Koduru et al, 1995;Uchida et al, 1995).…”
supporting
confidence: 73%
“…In lymphoid malignancies, the CDKN2 gene is inactivated mainly by homozygous deletions (Ogawa et al, 1995). However, we reported some point mutations in B-cell type non-Hodgkin's lymphomas (Uchida et al, 1995), and other investigators have also reported point mutations in acute lymphocytic leukaemia (Cayuela et al, 1996;Ohnishi et al, 1995;Quesnel et al, 1995) and chronic lymphocytic leukaemia (Haider et al, 1995;Otsuki et al, 1995). Thus, the CDKN2 gene appears to be inactivated by point mutations in some patients with lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations